Meningkatkan Motivasi Belajar dengan Model Pembelajaran Role-Playing Berbantuan Wordwall - Yesayas, Desi; Yohanes, Nathalia Yohanna; Mahananingtyas, Elsinora (Jurnal Pendidikan dan Ilmu Fisika, 2025)
This study aims to examine the impact of the implementation of the Role-Playing learning model assisted by the Wordwall educational game on the learning motivation of grade IV A students at SDN 1 Lateri. The method used is a quasi-experimental design with two groups: the experimental group, which applies the Role-Playing learning model assisted by Wordwall, and the control group, which uses conventional methods. The research subjects consisted of 36 students from grade IV A and IV B at SDN 1 Lateri. The instruments used to measure learning motivation include a questionnaire consisting of 18 valid and reliable statements, as well as an observation sheet. The results show a significant improvement in students' learning motivation in the experimental group after the model was applied, with indicators such as the desire to succeed, recognition in learning, and engaging activities in learning experiencing significant increases. In conclusion, the Role-Playing learning model assisted by Wordwall educational games is proven to be effective in enhancing students' learning motivation. The implications of this study are the importance of using innovative and technology-based learning models to increase student engagement, create a more interesting learning environment, and motivate students to learn more actively and effectively.